Civil society and government - Rosenblum, Nancy L.; Post, Robert C. (The Ethikon series in comparative ethics, 2002)
Machine generated contents note: Introduction -- Robert C. Post and Nancy L. Rosenblum -- State, Civil Society, and Classical Liberalism -- Steven Scalet and David Schmidtz -- Classical Liberalism and Civil Society: Definitions, History, and Relations -- Tom G. Palmer -- Civil Society and Government: A Liberal-Egalitarian Perspective -- Will Kymlicka -- Liberal Egalitarianism: A Family of Theories, Not a Single View -- William A. Galston -- A Critical Theory Perspective on Civil Society and the State -- Kenneth Baynes -- Skeptics at the Celebration: Civil Society and the Early Frankfurt School -- Stephen K White -- Feminist Perspectives on Civil Society and Government -- Nancy L. Rosenblum -- Comment on Nancy Rosenblum's "Feminist Perspectives on Civil Society and Government" -- Susan Moller Okin -- Natural Law, Civil Society, and Government -- Fred D. Miller, Jr. -- Natural Law: A Response -- William M. Sullivan -- A Limited State and a Vibrant Society: Christianity and Civil Society -- John A. Coleman, S.J. -- Christianity, Civil Society, and the State: A Protestant Response -- Max L. Stackhouse -- Civil Society and Government: Seeking Judaic Insights -- Noam J. Zohar -- Response to Noam Zohar -- David Biale -- Civil Society and Government in Islam -- John Kelsay -- Perspectives on Islam and Civil Society -- Farhad Kazemi -- Confucian Perspectives on Civil Society and Government -- Peter Nosco -- Commentary and Addenda on Nosco's "Confucian Perspectives on Civil Society and Government" -- Henry Rosemont, Jr. -- Overview: The Virtues and Vices of Civil Society -- Richard B. Miller